Enhancing Academic Competitiveness Through Strategic Curriculum Development Management - Rinrin Suryaningsih; Lilis Suwandari (Papanda Publisher, 2026)
Gaining entry into state universities through competitive selection mechanisms requires systematic academic preparation beyond individual aptitude, necessitating effective curriculum development management. However, misalignment between competency-based curriculum implementation and examination-focused selection requirements poses significant challenges for secondary schools. This qualitative case study examined curriculum development management at SMAN 1 Singaparna and SMAN 2 Singaparna using semi-structured interviews, systematic observations, and document analysis. Data were analyzed through Miles, Huberman, and Saldaña's interactive model involving data condensation, display, and conclusion drawing. Both institutions implemented systematic curriculum management through collaborative planning involving multiple stakeholders, coordinated organizational structures with clear role distribution, adaptive implementation integrating HOTS-based instruction with examination preparation, and multidimensional evaluation frameworks. Strategic responses to challenges included developing internal resource banks, establishing partnerships with online learning platforms, implementing alumni mentoring programs, and scheduling intensive preparation during post-examination periods. Despite infrastructure limitations, uneven teacher capacity, temporal constraints, and policy instability, both schools demonstrated organizational innovation and teacher agency in balancing comprehensive education with competitive examination preparation. Findings demonstrate that curriculum-assessment misalignment can be addressed through strategic integration at planning and implementation stages, extending curriculum management theory to competitive contexts and providing actionable insights for educational administrators navigating similar challenges while maintaining educational integrity.